2021
DOI: 10.1186/s13054-021-03496-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health-related quality of life and burden of disease after intensive care: development of a patient-reported outcome measure

Abstract: Background ICU survivorship includes a diverse burden of disease. Current questionnaires used for collecting information about health-related problems and their relation to quality of life lack detailed questions in several areas relevant to ICU survivors. Our aim was to construct a provisional questionnaire on health-related issues based on interviews with ICU survivors and to test if this questionnaire was able to show differences between ICU survivors and a control group. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Additionally, it would be interesting to examine support needs and self‐efficacy, as greater self‐efficacy has been associated with recovery after ICU 40 . Other new questionnaires are evolving which could assess long‐term health‐related quality of life after ICU and measure recovery 38,47 . Importantly, needs‐driven care should be based on patients' perceptions of need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it would be interesting to examine support needs and self‐efficacy, as greater self‐efficacy has been associated with recovery after ICU 40 . Other new questionnaires are evolving which could assess long‐term health‐related quality of life after ICU and measure recovery 38,47 . Importantly, needs‐driven care should be based on patients' perceptions of need.…”
Section: Discussionmentioning
confidence: 99%
“…We used an iterative and robust process to develop a patient-centred questionnaire to identify patient needs To date most services, when evaluated, generally use health-related quality of life measures or changes in physical or psychological morbidity rather than patient-identified needs. 14,38 To our knowledge, this is the first theoretically informed needs assessment questionnaire for ICU patients that can be used at different time points across the recovery trajectory. 4,15,[22][23][24]30 It is patient-focused and self-completed, enabling patients to identify their social support needs across informational, emotional, instrumental, appraisal, and spiritual domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the studies exploring appetite loss after discharge from the intensive care unit (ICU). An observational cohort study reported a high prevalence of appetite loss in patients discharged from the ICU compared to in age-and sexmatched non-ICU-treated patients [5]. However, this study has some limitations.…”
Section: Introductionmentioning
confidence: 83%
“…We read with interest the paper by Dr. Malmgren and co-workers addressing the issue of health-related quality of life (HRQoL) in former ICU patients [ 1 ]. We congratulate the authors for their excellent work, and especially in developing a questionnaire more adapted to depict effects on important areas of HRQoL in ICU patients.…”
mentioning
confidence: 99%
“…Finally, what can then be concluded from this study [ 1 ] with respect to constructing the questionnaire and what can be said about HRQoL in former ICU patients? The imbalance between comorbidities and socio-economic factors between the ICU and control cohorts diminishes the possibility to make robust conclusions regarding the critical care event itself and its potential effects on HRQoL.…”
mentioning
confidence: 99%